Chapter 24: Effects and explanations of active labour market policy: theoretical and empirical challenges for cross-national research - Cronert, Axel (Edward Elgar Publishing, 2023)
This chapter highlights and addresses some theoretical and empirical challenges in cross-national research on active labour market policy (ALMP). First, it highlights a number of connections and overlaps between ALMP and other analytical concepts. Second, it presents a brief state-of-the-art of the comparative ALMP research, focusing on (1) their macro-economic effects and (2) their political and economic explanations. Third, it argues that to advance scholarship in both these strands, scholars need to recognize that ALMPs are profoundly versatile policy tools that can be designed to trigger a variety of labour market transitions with distinct distributional consequences. Fourth, it spells out some theoretical and empirical implications of this argument for future research, including the importance of shifting from country-level analysis of ALMP to programme-level analysis. Fifth, the chapter previews a number of sparsely-used data sources on programme characteristics, reform events, and public opinion on ALMP that may pave the way for new advancements.